2020
DOI: 10.3390/catal10050586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Titanium Dioxide via Surfactant-Assisted Microwave Method for Photocatalytic and Dye-Sensitized Solar Cells Applications

Abstract: In this study, titania nanoparticles were obtained using the microwave-assisted technique. Moreover, different surfactants (PEG (Mn = 400), Pluronic P123 and Triton X−100) were used during the synthesis in order to determine their impact on the crystallinity and morphology of the final products. Subsequently, techniques such as XRD, SEM and TEM (performed in high contrast and high-resolution mode), diffuse reflectance spectroscopy (DRS), low temperature N2 sorption (BET model), FTIR and TGA were carried out. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…In order to produce improved materials with high surface area, several studies have focused on the synthesis of controlled porous TiO 2 -based materials with the addition of surfactants for the enhancement of photocatalytic activity [ 59 , 60 , 61 , 62 ]. Feng et al, reported enhanced metal-ion-doped TiO 2 photocatalysts under solar light with a large BET (Brunauer–Emmett–Teller) surface area, synthesized by microwave irradiation, through the use of the surfactant P123 [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce improved materials with high surface area, several studies have focused on the synthesis of controlled porous TiO 2 -based materials with the addition of surfactants for the enhancement of photocatalytic activity [ 59 , 60 , 61 , 62 ]. Feng et al, reported enhanced metal-ion-doped TiO 2 photocatalysts under solar light with a large BET (Brunauer–Emmett–Teller) surface area, synthesized by microwave irradiation, through the use of the surfactant P123 [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HR-TEM imaging focused mainly on TiO 2 particles for which the synthesis conditions have a determining the influence on the crystal growth. In HR-TEM and FFT images ( Figure 5 ), TiO 2 particles in TiO 2 -ZnO systems are correctly oriented with respect to the impinging electron beam showing lattice fringes 0.23 nm apart (d 004 = 0.2378 nm) [ 25 ]. Thus, they correspond to {001} surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The already described method has been used to prepare the viscous pastes of TiO 2 -ZnO systems [ 24 , 25 ]. The pastes containing selected TiO 2 -ZnO materials, terpineol, and ethylcellulose have been used to prepare working electrodes by spreading the pastes on fluorine-doped tin oxide glass (FTO) substrates using the “ doctor-blade ” technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4]. In order to be able to control the above parameters, it is necessary not only to apply innovative synthesis techniques (e.g., microwave route [110]) but also to use morphology-determining agents (e.g., hydrofluoric acid [111]). Despite the undoubted advantages resulting from the high photoactivity of titania, researchers are still looking for novel materials with similar or better parameters than TiO 2 .…”
Section: Other Magnetic-photocatalytic Compositesmentioning
confidence: 99%